The Viral Founder Effect and Economic-Driven Human Mobility Shaped the Distinct Epidemic Pattern of HIV-1 CRF01_AE in Northeast China - An, Minghui; Zhao, Bin; Wang, Lin; Chu, Zhenxing; Xu, Junjie; Ding, Haibo; Han, Xiaoxu; Shang, Hong (Frontiers in Medicine, 2021)
Background: In China, two distinct lineages shaped the epidemic of HIV-1 CRF01_AE among men who have sex with men (MSM), of which the uneven distributions were observed geographically. One lineage spread across China, while another dominated in Northeast China. Understanding the drivers of viral diffusion would provide guidelines for identifying the source and hotspots of HIV transmission among MSM to target interventions in China. Methods: We collected the pol sequences between 2002–2017 to reconstruct the spatiotemporal history of CRF01_AE lineages in Shenyang, one economic center of Northeast China, using the Bayesian phylogeographic and phylodynamic approaches. Importantly, for the datasets with the high sample density, we did the down-sampling to avoid the sampling bias. Results: Two lineages accounted for 97%, including 426 and 1516 sequences, and homosexuals and bisexuals were above 80%. One lineage appeared earlier 7 years than another (1993 vs. 2002) among homosexuals and bisexuals, whereas among heterosexuals, both lineages were observed firstly in 2002. 96% viral migrations within one lineage were from homosexuals toward bisexuals (49%) and male-heterosexuals (46%). Within another, except for homosexuals (72%), bisexuals (23%) served as the top second source, and female-heterosexuals (11%) were the third recipients following bisexuals (44%) and male-heterosexuals (39%). Although the basic reproduction number (R0) of two lineages were similar and both of the effective production number (Re) fell below 1 at the most recent sampling time, the starts of the Re declining varied. Conclusions: Our findings revealed that throughout the viral national spread chain, Shenyang is the source for the initial expanding of one lineage, where is only a sink of another, proving that the viral founder effect and regional human mobility contributed to the uneven distribution of two lineages, and emphasizing the important roles of the area where the virus originated and economy-driven migrants in HIV transmission.